(untitled) (Research, Society and Development, 2022)
The process of economic globalization and the way of organizing the current production and consumption system have generated profound changes in the environment that influence, including the loss of quality of life of the population. In the desire to reverse this situation, sustainable development has been widely discussed in various social spaces, including the school environment. Despite having its ethical and social role in promoting sustainability, a school represents a microcosm of society, collectors environmental aspects and impacts and to circumvent them it is necessary to manage them responsibly. In this sense, the objective of this research is to demonstrate that it is possible to build, for basic education school institutions, an Environmental Management System (SGA) based on the PDCA cycle, bringing suggestions on how to mitigate some aspects and showing that it is possible to use the system as a pedagogical resource. Through exploratory qualitative research, it was possible to develop the SGA proposal for school environments in five stages with suggestions of applicability to each of them.